2009
DOI: 10.1159/000196374
|View full text |Cite
|
Sign up to set email alerts
|

Intrathoracic Displacement of Pleuroamniotic Shunt after Successful in utero Treatment of Fetal Hydrops Secondary to Hydrothorax

Abstract: Background: Primary fetal pleural effusion can be associated with high perinatal morbidity and mortality, especially when it is associated with the presence of fetal hydrops. Pleuroamniotic shunting results in effective drainage and lung expansion which prolong the pregnancy and improve neonatal survival. Intrathoracic displacement of the shunt is a rare but a known complication of shunt insertion and can cause some infant morbidity. We present a case of successful antenatal treatment of primary fetal pleural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
1
14
0
1
Order By: Relevance
“…There is no evidence for which is best mode of delivery (vaginally or caesarean section), even if in rare cases it has been suggested the ex utero intrapartum treatment (EXIT) procedure too [25,28].…”
Section: Discussionmentioning
confidence: 99%
“…There is no evidence for which is best mode of delivery (vaginally or caesarean section), even if in rare cases it has been suggested the ex utero intrapartum treatment (EXIT) procedure too [25,28].…”
Section: Discussionmentioning
confidence: 99%
“…Large amounts of pleural fluid can compress the lung and heart and lead to abnormal lung development, fetal hydrops, and even fetal death. Pleuro-amniotic shunting has been utilized to improve perinatal outcomes [1,2,3,4,5]. However, the procedure is not without risks.…”
Section: Discussionmentioning
confidence: 99%
“…However, the procedure is not without risks. Known complications of shunting include ruptured membranes, preterm labor, shunt malfunction due to blockage, and shunt dislodgement both into the amniotic cavity and the fetal thorax [1,2,3,4,5]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors 13,14 have suggested conservative treatment without surgical removal. Their follow-up (24 and 12 months, respectively) did not revealed significant complications.…”
Section: Discussionmentioning
confidence: 99%